A logoterápia és az emberi életérték „mégis” öröme. Avagy boldoggá tehet-e az életértelem? - VIK, János (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Logotherapy and the „Defiant” Joy of Human Life-Value. Or Can the Meaning of Life Make You Happy? The starting point for this paper is the anthropology of Viktor E. Frankl, which, in addition to the physical and psychological dimensions, also considers the third one, the spiritual dimension of human being. Frankl believes that the most important motivation of man is to be found in his constant search for the meaning of life. In this context, the research question posed in this paper is: can finding concrete answers to the question of the meaning of life make man happy? In the first part of the paper, the concepts of “pleasure”, “joy”, and “happiness” are distinguished in the light of Frankl’s writings. In the second section, and in the light of the initial question posed, we come to the realization that the most important characteristic of people who have emerged unscathed from the most adverse circumstances is a kind of individualism and a strong sense of purpose, which, unlike narcissism and egocentrism of any kind, can forget itself. These are the people who have found joy in situations that ordinary people would have found unbearable.